Total Training for Adobe Acrobat X Pro essentials - Maivald, James J.; Safari eBooks ([S.l.] : Total Training, 2011)
"Total Training for Adobe Acrobat X Pro: Essentials online training will teach you the skills you need to master this new version of Adobe's powerful document management software."--Resource description page.
Title from resource description page (viewed July 26, 2011).
Publication information from end credits.
Presenter, James Maivald.
Producer, Barbara Stilwell Borrero, Barbara Ross ; director, Eric Vitner ; director video production, Barbara Ross ; art direction, Brian Maffitt ; director of creative services Barbara Driscoll ; quality assurance, Denise Maffitt ; technical consultant, Richard Lainhart ; executive producer, Brian Maffitt.
Keywords: Text processing (Computer science); Adobe Acrobat; Portable document software; PDF (Computer file format); Electronic books